Interactive Media Development Using Articulate Storyline-Based Instructional Games for Teaching Fractions - Vina Iman Adhiana; Yuniawatika Yuniawatika; Erif Ahdhianto; Jan Wantoro (Universitas Muhammadiyah Surakarta, 2022)
This research and development were carried out to produce valid and engaging interactive fractional learning media products using Articulate Storyline-based instructional games. This study used the type of research and development (RD) using the ADDIE model. The research subjects were the fifth-grader of State Elementary School 5 Saptorenggo Malang Regency. The techniques used in this study were validation questionnaires, observation, and interviews. Material experts, media experts, and teachers conducted a validity test to achieve a valid category result. The attractiveness test obtained a very high score and reached the very attractive category. The use of product development can improve student learning outcomes and provide an understanding of fractional material that is known from the value they get when doing practice questions and getting an average score above the Minimum Completeness Criteria. Thus, it can be said that this interactive media falls under the category of being appropriate for use in the learning process and being both valid and interesting. This research employed an Articulate Storyline-based learning game that covers the subject of mathematical fractions